RACISMO NA ESCOLA: um estudo da linguagem racista e de suas implicações no contexto escolar da UEB. Gonçalves Dias de Açailândia - MA - Almeida, Cleuma Maria Chaves de (2013)
In a society marked by illiteracy, the negative idea associated to certain signs like the Black is built by the racist culture and reproduced by everyday oral language. It confuses culturally made concepts with universal and natural ones. Thus, this piece of research addresses the language of racism, especially in its oral aspect, having the municipal elementary school Unidade Escolar de Educação Básica Gonçalves Dias in Açailândia MA as a locus. It aims to analyze what is being "black" in children‟s minds and to characterize the discrimination in the school environment, having the language as the tool for the construction (or destruction) of racism. The study was developed using the qualitative theoretical and methodological approach, focusing on search-action , and having as theoretical sources the works of Bourdieu (2010), Bakhtin (2009), Echeverria (2007), Munanga (1998), Moore (2007) and Sales (2008). In this context, it is possible to conclude that the oral language is a way to efficiently spread the pejorative meanings attributed to the black and a tool to consolidate cordial relationships of power. The study also identifies a witty talk capable of anesthetizing its victims precisely due to the friendship and to the lack of formality among the members of the group. This is efficient in reproducing stigmas that label the bodies and the social representation of the black people. It is noticed that in the considered school in theory an institution responsible for disseminating culture and knowledge and for the social interaction among individuals the spreading of an oral language filled with racist intents and meanings. Therefore it is through a discriminatory oral language that children assimilate racist values. Hence, the acknowledgment of the social and ethical effects of racism in schools, as well as its mean of dissemination, is necessary.